2023
DOI: 10.1002/aenm.202300932
|View full text |Cite
|
Sign up to set email alerts
|

A Generic “Engraving in Aprotic Medium” Strategy toward Stabilized Zn Anodes

Abstract: Zn foil pretreatment is a direct route to alleviating Zn anode instability and maintaining high energy performance in Zn metal batteries. Unfortunately, prevailing methods for achieving an ideal Zn surface texture do not enable durable operation under a large depth of discharge, thus impairing the Zn utilization ratio. Zn etching is a more feasible way to control the surface texture, but this approach remains relatively unexplored. In this study, a general strategy is reported for Zn foil engraving in aprotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The chronoamperometry (CA) analyses were further conducted to illustrate the Zn nucleation and growth behaviors (Figure 4b). [ 51 ] The current variation in the CA curves is closely related to the mode of Zn deposition and the change in surface morphology. For the HD‐OTf/Li electrolyte, the current density reaches an even state in a very short period of 25 s at an overpotential of −150 mV, indicating a stable 3D diffusion procedure on the surface, consequently inducing uniform Zn deposition.…”
Section: Resultsmentioning
confidence: 99%
“…The chronoamperometry (CA) analyses were further conducted to illustrate the Zn nucleation and growth behaviors (Figure 4b). [ 51 ] The current variation in the CA curves is closely related to the mode of Zn deposition and the change in surface morphology. For the HD‐OTf/Li electrolyte, the current density reaches an even state in a very short period of 25 s at an overpotential of −150 mV, indicating a stable 3D diffusion procedure on the surface, consequently inducing uniform Zn deposition.…”
Section: Resultsmentioning
confidence: 99%
“…The cyclic voltammetry (CV) curve (Figure S6, Supporting Information) showed that the onset potential for Zn plating on the M3DP-MXene/Cu- e) Comparison of the symmetric and asymmetric cell cycle life between the M3DP-MXene/Cu-THBQ/Zn-P and those in recent studies. [8,[12][13][14]16,[21][22][23][24][25][26][27][28][29][30][31][32][33] Exsitu SEM images of f-h) bare Zn-P anode and i-k) M3DP-MXene/Cu-THBQ/Zn-P anode. l) LCSM image of bare Zn-P anode and m) M3DP-MXene/Cu-THBQ/Zn-P anode.…”
Section: Investigations Of Cycling Stability and Zn Deposition Behavi...mentioning
confidence: 99%
“…Encouragingly, the long cycle life of the M3DP-MXene/Cu-THBQ/Zn-P anode exceeded that of most previous reports on the modification of Zn-P anodes (Figure 3e). [8,[12][13][14]16,[21][22][23][24][25][26][27][28][29][30][31][32][33] More intuitive evidence for the modulation of the Zn plating/stripping behaviour by MXene/Cu-THBQ was obtained using ex-situ SEM. For the bare Zn-P anode, numerous flake-like dendrites appeared on its surface after 100 h. As the cycle time increased to 220 h, a more ragged and thicker Zn dendrite layer was formed owing to the uneven Zn deposition and side reactions (Figure 3f,h).…”
Section: Investigations Of Cycling Stability and Zn Deposition Behavi...mentioning
confidence: 99%
“…In general, a standalone manufacturing technology is highly unlikely to address all the existing challenges faced by LIBs . The limitation of lithium resources has led to exploration of alternative devices such as sodium-ion and potassium-ion batteries, as well as sodium/potassium/zinc metal batteries, which utilize more abundant natural resources. Furthermore, the safety of LIBs has always been an issue of concern. One approach to address this challenge is replacing the flammable organic electrolytes by aqueous electrolytes. , Solid-state electrolytes have also shown promise in enhancing battery safety.…”
Section: Emergence Of Printable Energy Storagementioning
confidence: 99%